Examinations in Singapore : change and continuity (1891-2007) - Tan, Yap Kwang (World Scientific, 2008)
The first book to explore the development of Singapore's much-talked-about education and examination system, this volume juxtaposes examinations with its immediate context of education and wider context of politics, economy and society. The study covers three broad historical periods: Examinations in Singapore from 1891 to 1945; The Post-War Years from 1946 to the 1970s; and Charting Our Destiny from the 1980s to 2007. In the British period up to 1941, the local examinations were conducted by the vernacular schools, and external examinations by the University of Cambridge Local Examinations Syndicate. There was a lack of systematic effort to establish a uniform system of education and examinations. During the Japanese Occupation, examinations were conducted by the Japanese authorities and, unexpectedly, the Cambridge examinations continued in the Sime Road Camp. In the post-war period and particularly after Singapore was granted self-government, the establishment of a national education system was followed by the emergence of national examinations: the Primary School Leaving Examinations and the Singapore-Cambridge GCE N/O/A Levels for every school-going child in Singapore. Thereafter, the nature of national examinations evolved with the changing needs of education and the nation. At the turn of the century, with the Ministry of Education's decision to take greater control of examinations, the Singapore Examinations and Assessment Board was established, to oversee new developments in examinations. Unlike most literature on education where examinations are often mentioned as an outcome of educational goals and objectives, this book focuses on examinations per se. Examinations have gained a momentum of their own, and it is interesting to note the development of examinations against the backdrop of the broader history of Singapore and of education in Singapore.